Takotsubo Syndrome: An International Expert Consensus Report on Practical Challenges and Specific Conditions (Part-2: Specific Entities, Risk Stratification and Challenges After Recovery) - Kenan Yalta; John E Madias; Nicholas G Kounis; Shams Y-Hassan; Marija Polovina; Servet Altay; Alexandre Mebazaa; Mehmet Birhan Yilmaz; Yuri Lopatin; Mamas A Mamas; Robert J Gil; Ritu Thamman; et al. (Balkan Medical Journal)
Takotsubo syndrome (TTS) still remains as an enigmatic phenomenon. In particular, long-term challenges (including clinical recurrence and persistent symptoms) and specific entities in the setting of TTS have been the evolving areas of interest. On the other hand, a significant gap still exists regarding the proper risk-stratification of this phenomenon in the short and long terms. The present paper, the second part (part-2) of the consensus report, aims to discuss less well-known aspects of TTS including specific entities, challenges after recovery and risk-stratification.